Cisco CCNA 200-125 : the complete guide to getting certified (Packt Publishing, 2018)
"If you want to jumpstart your career in IT and networking by acing the Cisco CCNA exam, then this course is for you! It gives you a full understanding of all the concepts and topics you need to earn the most in-demand networking certification today by passing the Cisco CCNA Routing and Switching 200-125 exam. This course offers an easy to understand, structured approach to shortcut your path to mastering Cisco networking to the CCNA level and beyond. In this course, you won't just gain the book smarts to pass the exam. You'll also hone your hands-on skills to succeed as a network engineer in the real world. If you take a comparable course at a training center it will cost you thousands of dollars, and when it's over you can't experience the tutorials again or ask the instructor any more questions. When you take my course you can learn anytime you want in the comfort of your own home, and I'm always here for you whenever you need any help."--Resource description page